2011
DOI: 10.1186/1752-153x-5-42
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of molybdenum oxide nitrides as model systems for selective oxidation catalysts

Abstract: Molybdenum oxide nitride (denoted as Mo(O,N)3) was obtained by ammonolysis of α-MoO3 with gaseous ammonia. Electronic and geometric structure, reducibility, and conductivity of Mo(O,N)3 were investigated by XRD, XAS, UV-Vis spectroscopy, and impedance measurements. Catalytic performance in selective propene oxidation was determined by online mass spectrometry und gas chromatography. Upon incorporation of nitrogen, Mo(O,N)3 maintained the characteristic layer structure of α-MoO3. XRD analysis showed an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…This resembles the procedure described by Kühn et al [49]. Afterwards the resulting material was calcined at 550 °C for 4 h like all the other samples.…”
Section: I(060) + I(021)mentioning
confidence: 99%
“…This resembles the procedure described by Kühn et al [49]. Afterwards the resulting material was calcined at 550 °C for 4 h like all the other samples.…”
Section: I(060) + I(021)mentioning
confidence: 99%
“…Thep reedge peak heights of in situ Va nd Mo K-edge XANES spectra at 298 K( Figure 4) were attributed to the distorted MO 6 (M = V, Mo) building units of the Keggin ion with the metal centers in their highest oxidation states. [5,21] The XANESs pectra remained unchanged in the temperature range 298-473K.H ence, the Keggin structure appeared to be stable up to 473 K. Between 473 and 648 K, the pre-edge peak heighti ncreased with temperature. This indicated structural changes from octahedral to tetrahedral [MO x ]( M = V, Mo) units during thermal treatment under catalytic conditions.…”
mentioning
confidence: 87%
“…Resulting oxide nitrides represent suitable model system for studyingc orrelations between oxygen mobility and catalytic performance. [13] The corresponding oxide nitrides of a-MoO 3 exhibited an enhanced electronic conductivity. [14] In addition, mild ammonolysis resulted in am uch improvedr educibility,w hich can be attributed to increased oxygen mobility.C orrelations between catalytic performance and electrical properties could not be elucidated because of the low thermals tability of the corresponding oxide nitrides.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that nitrogen can be incorporated in the anion lattice of α‐MoO 3 without changing the crystallographic structure. Resulting oxide nitrides represent suitable model system for studying correlations between oxygen mobility and catalytic performance . The corresponding oxide nitrides of α‐MoO 3 exhibited an enhanced electronic conductivity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation